Pandangan Gereja Katolik Terhadap Perkawinan Campur Perspektif Amoris Laetitia Dan Hukum Kanonik - Nikodemus, Nikodemus; Endi, Yohanes (Kamaya: Jurnal Ilmu Agama, 2023)
This study focuses on Interfaith Marriages, where marriage occurs between two individuals with different religious beliefs. In the context of the Catholic Church, interfaith marriages are categorized into two types: interfaith marriages and inter-church marriages. Interfaith marriage involves a Catholic marrying a non-baptized individual of another faith, while inter-church marriage involves a Catholic marrying a non-Catholic who has already been baptized. This phenomenon has complex implications, in terms of religion, society, and law. Therefore, this research aims to provide an overview of interfaith marriages by presenting the Catholic perspective and legal aspects of the phenomenon in Indonesia. This study also seeks to understand the Catholic Church's views on interfaith marriages based on the perspective presented in Amoris Laetitia. The research employs a document analysis method to analyze documents such as Amoris Laetitia, Canon Law, and Civil Law. This method involves a careful examination of these documents to understand the Catholic Church's stance on interfaith marriages. In preparing for interfaith marriages, there are several demands placed on the couples, such as pledging to maintain their faith, striving to raise their children in the Catholic tradition, and more. Additionally, couples must be capable of addressing conflicts that may arise due to religious differences while strengthening a relationship built on mutual respect and support. From a legal perspective, both Canon Law and civil law regulate interfaith marriages, with Canon Law prohibiting interfaith marriages due to potential negative effects. However, for compelling reasons, the Church provides flexibility in conducting interfaith marriages. This research underscores the importance of thorough preparation and a clear understanding of the rights and responsibilities of couples in interfaith marriages. The Catholic Church, as stated in the document Amoris Laetitia, endeavors to promote happiness and stability in interfaith marriages while upholding Catholic values and teachings.